2006
DOI: 10.1152/ajpheart.00529.2006
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced oxidative stress in kidneys of salt-sensitive hypertension: role of sensory nerves

Abstract: To determine the mechanism(s) underlying enhanced oxidative stress in kidneys of salt-sensitive hypertension, neonatal Wistar rats were given vehicle or capsaicin (CAP, 50 mg/kg sc) on the first and second days of life. After being weaned, male rats were assigned into four groups and treated for 2 wk with the following: vehicle + a normal sodium diet (NS, 0.4%, CON-NS), vehicle + a high-sodium diet (HS, 4%, CON-HS), CAP + NS (CAP-NS), and CAP + HS (CAP-HS). Systolic blood pressure was significantly increased i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 48 publications
(66 reference statements)
3
20
0
Order By: Relevance
“…Because of the important relationship between Klotho gene and oxidative stress, we have focused on renal oxidative stress in SHR. Renal oxidative stress has been detected in several hypertension models [21,22] . Experimental studies have established a role for oxidative stress in hypertensive renal damage and the therapeutic potential of antioxidant treatment [23,24] .…”
Section: Discussionmentioning
confidence: 99%
“…Because of the important relationship between Klotho gene and oxidative stress, we have focused on renal oxidative stress in SHR. Renal oxidative stress has been detected in several hypertension models [21,22] . Experimental studies have established a role for oxidative stress in hypertensive renal damage and the therapeutic potential of antioxidant treatment [23,24] .…”
Section: Discussionmentioning
confidence: 99%
“…These data show that selective knockdown of neuronal TRPV1 enhances prohypertensive effects induced by salt loading and that pressor effects of TRPV1 shRNA may be mediated, at least in part, by enhancement of the sympatho-excitatory response. We have previously shown that neonatal degeneration of TRPV1-expressing sensory nerves increased salt sensitivity of arterial pressure as these rats grew into adulthood [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . However, the systemic sensory denervation used in these previous studies precluded us from making conclusions about whether the observed effect was due to the removal of TRPV1 or other proteins co-expressed in the same nerves innervating any specific organs or tissues [21,22] .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, defining the role of TRPV1-positive sensory nerves in the regulation of blood pressure and salt sensitivity will be useful. We have shown previously that the degeneration of TRPV1-expressing sensory nerves throughout the neonatal body by subcutaneous injection of capsaicin, a selective TRPV1 agonist, leads to increased salt sensitivity of arterial pressure, indicating that TRPV1-positive sensory nerves play a counter-regulatory role against salt-induced increases in blood pressure [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . The underlying mechanism of anti-hypertensive effects of TRPV1 may involve its counter-balancing role against the activation of the renin-angiotensin-aldosterone system [7][8][9] , sympathetic nervous system [10] , endothelin system [11,12] , superoxide generation system [13,14] , and epithelial sodium transporters [15] .…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, renal afferent innervation was linked to the amelioration of the consequences of oxidative stress (38). In rats with destruction of afferent sensory nerves due to early postnatal capsaicin treatment, enhanced O 2 Ϫ could be measured in the cortex and medulla of the kidney if these animals were on a high-salt diet.…”
Section: Discussionmentioning
confidence: 99%